The Sentences of the Syriac Menander Introduction, Text and Translation, and Commentary - Monaco, David Gregory (Gorgias Studies in Classical and Late Antiquity, 2013)
The Sentences of the Syriac Menander appears in two Syriac manuscripts in the British Library, a full version in one codex, and a far shorter version, only a small fraction thereof, in another. This book presents a commentary on the text in its complete version focusing on parallels from both Jewish tradition and the Greco-Roman world, showing that the text is not, as it claims, the work of the Greek author Menander, but rather a work of Jewish Wisdom Literature composed in Syriac, possibly in the ancient city of Edessa itself, and preserved within Christian monastic circles